Development of STEAM-Based Integrative Learning Tools on The Topic of Islamic Mathematization - kusno kusno (Asian Journal of Social and Humanities, 2023)
Integrative learning that integrates spiritual and social attitudes with knowledge and skills has become an interesting discussion in the world of education. However, in the mathematics education study program the application of this learning is less familiar because it is difficult to find references on the integration of mathematics with spiritual and social values. The purpose of this study is to develop a STEAM-based integrative learning tool for effective Islamic Mathematization. This research is an R&D research using the 4 D model (Define, Design, Develop and Dessimenate) from Thiagarajan which is simplified to the develop stage. The test subjects were 31 students who took courses on the integration of Islam and science at the Mathematics Education Study Program, University of Muhammadiyah Purwokerto, Central Java, Indonesia for the 2020/2021 academic year. Data collection tools using expert validation sheets, student response questionnaires and Learning Outcomes Tests. The results showed that the validity of STEAM-based integrative learning tools was 83.5% (valid), 85% positive student responses, 84% learning completeness (completed), and the recommendations from the validator were 80% (feasible to use) so that the learning tools it's effective. Therefore, it can be used to enrich the treasures of holistic learning in mathematics education study programs.